2004
DOI: 10.1038/sj.onc.1208178
|View full text |Cite
|
Sign up to set email alerts
|

Strand invasion involving short tract gene conversion is specifically suppressed in BRCA2-deficient hamster cells

Abstract: The BRCA2 tumour suppressor protein is involved in maintaining genetic stability through its role in homologous recombination (HR), where it mediates RAD51-dependent strand invasion. Here, we show that BRCA2-defective cells are not completely impaired in HR by strand invasion although the spontaneous HR rate is 10-fold lower than that in wild-type cells. Furthermore, a DNA double-strand break (DSB) triggers HR repair by strand invasion also in BRCA2-defective cells, but less efficiently. Thus, either the stran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…We confirmed that an I-SceI-induced DSB produces mainly short-tract gene conversion products (Fig. 3B) (16,35). This is consistent with current models for homologous recombination triggered by DSBs, resulting in gene conversion (see Fig.…”
Section: Resultssupporting
confidence: 77%
“…We confirmed that an I-SceI-induced DSB produces mainly short-tract gene conversion products (Fig. 3B) (16,35). This is consistent with current models for homologous recombination triggered by DSBs, resulting in gene conversion (see Fig.…”
Section: Resultssupporting
confidence: 77%
“…HR was investigated in four independently isolated CL-V4B clones following transient transfection with the pCMV3xnlsI-SceI vector, encoding the I-SceI restriction endonuclease, to make a DSB. Recombinant clones were selected with G418 and we found that the HR frequencies are overall lower in the RAD51C deficient cells as compared with V79 wild type control from earlier experiments ( Table 2 ) (Saleh-Gohari and Helleday, 2004). Also, the pooled data showed that HR in RAD51C deficient CL-V4B cells is significantly reduced as compared with HR in the corresponding wild type cells ( Fig.…”
Section: Rad51c Is Involved In Homologous Recombinationmentioning
confidence: 82%
“…This model explains the observed B-cell development defect in Xrcc2 Ϫ/Ϫ cells, as well as the early S-phase cell cycle arrest, and is supported by several additional lines of evidence. First, there is accumulating data that HR factors are required for replication fork restart following stalling or regression (28)(29)(30). Second, Xrcc2 is required, at least in some cells, for resistance to hydroxyureainduced replication stress (14).…”
Section: Discussionmentioning
confidence: 99%